Marine ornamental species aquaculture - Calado, Ricardo; Olivotto, Ike; Oliver, Miquel Planas; Holt, J. (Joan) (Chichester, West Sussex, UK : Wiley-Blackwell, 2017)
The global trade of aquatic organisms for home and public aquariums, along with associated equipment and accessories, has become a multi-billion dollar industry. Aquaculture of marine ornamental species, still in its infancy, is recognized as a viable alternative to wild collection as it can supplement or replace the supply of wild caught specimens and potentially help recover natural populations through restocking. This book collects into a single work the most up-to-date information currently available on the aquaculture of marine ornamental species. It includes the contributions of more than 50 leading scientists and experts on different topics relevant for the aquaculture of the most emblematic groups of organisms traded for reef aquariums. From clownfish, to angelfish, tangs and seahorses, as well as corals, anemones, shrimps, giant clams and several other reef organisms, all issues related with the husbandry, breeding, and trade are addressed, with explanatory schemes and illustrations being used to help in understanding the most complex topics addressed. Marine Ornamental Species Aquaculture is a key reference for scientists and academics in research institutes and universities, public and private aquaria, as well as for hobbyists. Entrepreneurs will also find this book an important resource, as the culture of marine ornamental species is analyzed from a business oriented perspective, highlighting the risks and opportunities of commercial scale aquaculture of marine ornamentals.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed February 22, 2017).
Keywords: Marine aquarium animals; Ornamental fishes; Aquaculture; TECHNOLOGY & ENGINEERING / Agriculture / General; Aquaculture; Marine aquarium animals; Ornamental fishes; Electronic books